The Evolution of Artificial Intelligence in Accounting and Auditing: A Bibliometric Analysis Review - Fandi Prasetya; Khalilah Nafisah; Vidya Intani Athfalina (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2026)
This research aims to map the intellectual landscape of Artificial Intelligence (AI) in the accounting and auditing fields to identify publication trends, key actors, and emerging themes as future research agendas. The methodology employed is bibliometric analysis and science mapping of 751 documents sourced from the Scopus database for the period 2015–2025. Data visualization was performed using VOSviewer software to analyze bibliometric networks and thematic evolution. The results indicate a significant upward trend in publications, particularly a surge from 2024 to 2025. The United States dominates global publications, while Miklos Antal Vasarhelyi is the most productive author. Network analysis identified seven primary clusters covering topics such as accounting education, AI adoption, deep-learning-based auditing, and digital transformation. Current trends show a shift in focus from routine automation toward the use of generative AI and human resource readiness. This study concludes that AI integration has rapidly evolved from theoretical discourse to complex practical implementation. Future research agendas should emphasize the human element, specifically the adaptation of accounting education curricula and individual technological readiness.